(untitled) (Singapore, 1981)
This pattern of growth has been termed "Export-led industrialisation & development" in recognition of the leading roles played by both exporrt growth and industrialisation in the process.
Keywords: Industrialization,Asia,Công nghiệp hoá,Châu Á; Economic conditions,Điều kiện kinh tế; Asia,Châu Á